Burrowing pattern and damage caused by the rodent pest, Indian house rat (Rattus rattus) in the Gangetic and Non Gangetic plain of West Bengal, India - Chattopadhyay, Debiprasad; Madhu, Nithar Ranjan; Manna, Chanchal Kumar (University Journal of Zoology, Rajshahi University, 2010)
Key words: Burrowing pattern; hoarding materials; Gangetic and non Gangetic plain; laterite; alluvial. DOI: 10.3329/ujzru.v28i0.5288 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 57-60